Niger : Staff Report for the 2011 Article IV Consultation. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2011)
Niger's government has adopted an ambitious development plan, based on the use of oil and mining revenue for public investment in infrastructure, agriculture, health, and education. IMF staff underlined the need to step up efforts to improve the business climate in Niger to attract more jobs, thereby creating private investment in the nonnatural resources sector of the economy. Expanded reliance on revenues from natural resources will increase Niger's vulnerability to commodity price fluctuations, augmenting the high vulnerability to climatic shocks.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet